Implementation of Human Resource Management to Face the Era of Society 5.0 - Aulia, Fitria Anggun Tri; Anis; Janwaroh Hasbi Ansari; Iriani Ismail (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid development of science has brought many changes to humans, one of which is the era of society 5.0. Therefore, adequate human resource management is needed to deal with this. This research aims to find out the role of HR management in facing the era of society 5.0. The method used is descriptive qualitative and uses Cafe The Sky Bangkalan as a research location. From the results of data collection, it can be concluded that HR management can be useful in dealing with technological advances. Through HR management, employees will be better prepared to face changes resulting from the society 5.0 era and can improve the quality of their human resources